Impact of multiple sclerosis symptoms survey: Patient-reported data on the prevalence, burden, and management of multiple sclerosis symptoms in Europe - Peter Feys; Patricia Moghames; Elisabeth Kasilingam; Rachel King; Tommaso Manacorda; Magda Fonseca; Emma Rogan; Daphne Kos (Multiple Sclerosis Journal, 2026)
Background: To optimize the care of people with multiple sclerosis in Europe, the European Multiple Sclerosis Platform aimed to gather vital evidence from people with multiple sclerosis to understand prevalence, burden, and symptom management. Methods: An online survey was distributed by 24 European Multiple Sclerosis Platform–associated multiple sclerosis organizations across 22 countries. Descriptive statistics were applied. Results: Data from 17,151 people with multiple sclerosis revealed a mean of 13.7 symptoms. The five most prevalent symptoms included fatigue, sensory problems, sleep disturbances, cognitive impairment, and balance problems (range = 75%–93%). Respondents utilized a mean of 5.6 concurrent care modalities/strategies for symptom management, and 86% of them received disease-modifying drugs. They consulted a mean of 4.2 healthcare professionals for symptom management, with 50% experiencing coordination of care. Overall, 50% of respondents expressed satisfaction with their symptom management. However, satisfaction levels varied depending on the specific symptom: people with multiple sclerosis were twice as likely to report satisfaction with managing mobility, bladder control, and spasticity compared to managing sexual problems, fatigue, and cognitive impairment. Conclusion: This survey provides evidence of the high prevalence, burden, and impact of symptoms in people with multiple sclerosis, highlighting the need for multifaceted care strategies. The results call for a change in healthcare policies and practices.